Analysis of the Use of Attractor Technology in Catching Squid (Loligo sp.) in the Makassar Strait - Merliana Merliana; Wayan Kantun; Arnold Kabangnga (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Squid is one of the marine fisheries commodities that is widely liked by the public, causing an increase in demand and making squid production in the country quite large. This study aims to determine the composition, size distribution and productivity of catches in different attractor colors. Sampling was carried out in the waters of the Makassar Strait with 12 repetitions of three attractor treatments. This research is included in quantitative research with the capture experiment method. The data obtained were described descriptively by referring to the treatment of different attractor colors. The results showed that the composition of the catch during 12 trips amounted to 149 fish with details of 16.11% caught in white attractors, 32.21% caught in black attractors and 51.68% caught in blue attractors. The distribution of weight measurements captured based on different attractor colors obtained the highest results in blue attractors, which was in the weight range of 15-95 g (46.62 ± 21.93 g). The distribution of the length of the coat captured based on the color of different attractors obtained the highest results in black attractors, which was in the range of 7.5-20 cm (10.33 ± 2.34 cm) in length. The squid caught is predominantly medium-sized.